Recent Seismic Sequences and Activation of Normal Fault Systems in the Mugello Basin and Surrounding Areas (Northern Apennines, Italy) - Saccorotti, Gilberto; Bruni, Rebecca; Bonini, Marco; Corti, Giacomo; Keir, Derek; Sani, Federico (Frontiers in Earth Science, 2022)
The Mugello Basin (North-Eastern Tuscany) is an intramontane basin of the Northern Apennines (Italy) with a well-documented record of seismicity; the two major historical earthquakes occurred in 1542 (Mw=6.0) and in 1919 (Mw=6.4). In this study, we integrate different seismic catalogs spanning the 2005-2019 time interval, and complement these data with phase arrival times from a temporary network that specifically operated in the area throughout the 2019-2021 time interval. The subsequent relocation of this data set with a double-difference algorithm allows for accurate analyses of the most relevant seismic sequences which affected the study area in 2008, 2009, 2015-2017 and 2019. These sequences are associated with the activation of adjacent segments of larger NW-striking fault systems, one of which bounds the NE margin of the Mugello Basin (Ronta Fault System). For each seismic sequence, best-fit fault surfaces are derived from orthonormal regression of relocated hypocenters, yielding consistent results with that derived from fault plane solutions. The four sequences occurred after a period of almost 50 years of quiescence. This suggests that, following the 2008 renewal of seismicity, static or dynamic stress changes, or both depending on the case, played a role in advancing the time of failure of the fault segments activated subsequently.